Haematococcus pluvialis Microalgae Extract Inhibits Proliferation, Invasion, and Induces Apoptosis in Breast Cancer Cells - Alateyah, Nouralhuda; Ahmad, Salma M. S.; Gupta, Ishita; Fouzat, Arij; Thaher, Mahmoud Ibrahim; Das, Probir; Al Moustafa, Ala-Eddin; Ouhtit, Allal (Frontiers in Nutrition, 2022)
Breast cancer (BC) is the most common malignant cancer in females worldwide. Drug resistance, toxicity, and the failure of current therapies to completely cure BC has challenged conventional medicine. Consequently, complementary alternative medicine has become popular due to its safety and efficacy. Haematococcus Pluvialis (H. pulvialis) is a green microalga living in fresh water, and its crude extract is rich of bioactives, including carotenoids, known to inhibit cancer cell growth. In the present study, we investigated the effects of a methanol crude extract called “T1” of H. pulvialis on cell growth and migration/invasion of the BC cell line MDA-MB-231 in comparison to the fibroblast control cells. TI significantly suppressed BC cell growth, inhibited migration and invasion and induced apoptosis. Interestingly, apoptosis was mediated by a significant loss of mutant p53 protein, and increased Bax/Bcl2 ratio. Our findings support our hypothesis that T1 exerts its anti-cancer effects by inhibiting BC invasion and inducing apoptosis mediated, at least, via the p53/Bax/Bcl2 pathway. Ongoing experiments aim to identify the molecular mechanisms underpinning T1-inhibited BC cell invasion using pre-designed metastasis gene-based array method.